SPEXIN LEVEL IN ACUTE MYOCARDIAL INFARCTION IN THE EMERGENCY DEPARTMENT - Ciftci, Yahya; Gurger, Mehtap; Gul, Evrim; Yilmaz, Mustafa; Telo, Selda; Atescelik, Metin; Kobat, Mehmet Ali (Soc Medical Biochemists Serbia, 2023)
Background: We aimed to determine the serum spexin level in patients with acute myocardial infarction (AMI) admitted to the emergency department. Methods: A total of 100 patients with AMI (50 with ST -segment elevation myocardial infarction (STEMI) and 50 with non-ST-segment elevation myocardial infarction (NSTEMI)) and 50 control group patients with non-cardiac chest pain were included in the study. A detailed anamnesis was taken, a physical examination was performed, and 12-lead electrocardiograms and venous blood samples were taken at the time of admission. Spexin levels were measured via enzyme-linked immunosorbent assay. Results: Serum spexin levels were significantly lower in the AMI group than in the non-cardiac chest pain group (p<0.001). There was no significant difference in serum spexin levels between STEMI and NSTEMI patients (p=0.83). In receiver operating curve analysis, we detected 58% sensitivity, 76% specificity, 82.9% positive predictive value, and 47.5% negative predictive value with an optimal cutoff value of 532 pg/mL for the diagnosis of AMI. Conclusions: In this study, serum spexin levels were significantly lower in AMI patients compared to patients with non-cardiac chest pain. The decrease in spexin levels suggests that it has the potential to be used as a diagnostic marker in AMI patients.
Keywords: spexin; acute myocardial infarction; diagnosis